Autonomy supportive and controlling leadership as antecedents of work design and employee well-being - Pallavi Sarmah; Anja Van den Broeck; Bert Schreurs; Karin Proost; Filip Germeys (BRQ Business Research Quarterly, 2022)
The continuation of work that undermines employee well-being necessitates an investigation into the antecedents of work design. Therefore, we examined how autonomy supportive and controlling leadership - as defined in self-determination theory (SDT) - relate to employees' job resources, job demands, and well-being. Using a cross-sectional (N = 501) and a daily diary study (N = 123), we found that autonomy supportive leadership relates to employees' work engagement via job resources both at the between- and within-person levels. However, only the cross-sectional study evidenced a relationship between autonomy supportive leadership and exhaustion via job resources. Controlling leadership related to exhaustion via job demands at the between-person level in both studies but not at the within-person level. Alongside implications for the literature on SDT, work design theory, the leadership literature, and workplace re-enchantment, we advance concomitant insights to practitioners.
Keywords: I31; J81; M12; 650; Autonomy supportive leadership; controlling leadership; employee well-being; job demand resources model; self-determination theory